Existence and Uniqueness of Solution for COVID-19 Model as an Application of Fractional Differential Equation - Jwan S. Ali; Hero W. Salih (Academic Science Journal)
In this work, we study an impulsive mathematical model proposed by Ndaïrou et al [1]to describe the dynamics of COVID-19 model. To improve our understanding of this biological phenomenon that has emerged in China in recent years and then spread throughout the world. Has resulted in the death of millions of people. We the existence and uniqueness of the model for show that the model has the unique solution by using and proving some theorems. These theories help us to establish the patient's condition and its recovery in a hurry.